2023
DOI: 10.1038/s41598-023-33484-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of infliximab/tocilizumab versus tocilizumab among COVID-19 patients with cytokine storm syndrome

Abstract: Coronavirus Disease 2019 (COVID-19) continues to spread rapidly. Monoclonal antibodies as well as anti-tumor necrosis factor are considered promising treatments for COVID-19. A prospective cohort study in which patients are divided into three groups. Group 1: moderate and severe COVID-19 patients received standard treatment; Group 2: moderate and severe COVID-19 patients received tocilizumab; Group 3: moderate and severe COVID-19 patients received treatment with infliximab and tocilizumab. 153 patients were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A recent study showed that moderate to severe COVID-19 patients benefitted more from the administration of tocilizumab and another immunosuppressive medication called infliximab, in addition to the standard treatment [153]. However, one therapeutic agent may not be sufficient to improve multifarious outcomes in various stages of a disease.…”
Section: Future Perspectives: Potential Aims and Experimental Methodsmentioning
confidence: 99%
“…A recent study showed that moderate to severe COVID-19 patients benefitted more from the administration of tocilizumab and another immunosuppressive medication called infliximab, in addition to the standard treatment [153]. However, one therapeutic agent may not be sufficient to improve multifarious outcomes in various stages of a disease.…”
Section: Future Perspectives: Potential Aims and Experimental Methodsmentioning
confidence: 99%
“…We have previously shown that important pro-inflammatory cytokines, such as TNF, IL-6, IL-1β, and IFN-γ, were present at excessive concentration in the mouse lungs during MHV-3 infection and account for disease severity [24]. In line, inhibition of cytokines signaling has been shown to protect mice from MHV-3 infection [24,43], as well as mitigate damage in human cells and organs caused by SARS-CoV-2 [44,45]. As shown in Figure 4, there was an increase in the intrapulmonary concentrations of TNF, IL-6, IL-1β, and IFN-γ at 3 dpi, in the STD group.…”
Section: Vitamin D Mitigates Inflammation and Acute Lung Damage Induc...mentioning
confidence: 95%
“…The repurposed antiviral drugs used to treat COVID-19 may provide protection against infection or speed up recovery, but all COVID-19 antiviral drugs currently on the market have drawbacks that may prevent their use by the general public [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For example, remdesivir administration led to mild to moderate undesirable outcomes, including but not restricted to liver toxicity, queasiness, anemia, kidney impairment, low blood pressure, respiratory collapse, and constipation, among other things [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%